2016
DOI: 10.5812/ircmj.25760
|View full text |Cite
|
Sign up to set email alerts
|

Food Reduction in Avicenna’s View and Related Principles in Classical Medicine

Abstract: ContextTraditional Iranian medicine (TIM) is a rich and valuable school of thought that believes medications are not the only effective approach for the treatment of diseases but that nutrition is also important.Evidence AcquisitionOur study includes two parts; the first is a book review of the Canon of Medicine by Avicenna (10th and 11th centuries), in which we focus on finding and understanding Avicenna’s point of view. In the second part, we searched for “food reduction” as a key word from 2000 to 2015 in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…To su pokazali obrasci Mediteranske ishrane i Dietary Approaches to Stop Hypertension (DASH) [4]. Najnovija istraživanja iz 2016. godine, koja su sprovedena kroz Tehran Lipid and Glucose Study [5] su takodje pokazali značaj principa i mehanizama redukcione niskoproteinske dijete [6]. Na osnovu meta analize koju su uradili Pan i saradnici iz 2008. godine, pregledanjem 8 randomizovanih kontrolisanih kliničkih studija, shvaćeno je da je RNP dijeta od velikog značaja za smanjenje razvoja CKD [7].…”
Section: Uvodunclassified
“…To su pokazali obrasci Mediteranske ishrane i Dietary Approaches to Stop Hypertension (DASH) [4]. Najnovija istraživanja iz 2016. godine, koja su sprovedena kroz Tehran Lipid and Glucose Study [5] su takodje pokazali značaj principa i mehanizama redukcione niskoproteinske dijete [6]. Na osnovu meta analize koju su uradili Pan i saradnici iz 2008. godine, pregledanjem 8 randomizovanih kontrolisanih kliničkih studija, shvaćeno je da je RNP dijeta od velikog značaja za smanjenje razvoja CKD [7].…”
Section: Uvodunclassified
“…Lifestyle modification is made by making changes in the six essential principles of life, including air, food, and drink, sleep and awakening, body motion and rest, absorb the necessary ingredients and waste disposal of the body and mental states [13]. The first step in the treatment of diseases and lifestyle modifications is to select the appropriate diet for each patient, and the quality of food is considered for everyone, whether healthy or sick, in addition to the amount of food [12,14]. The importance of food measure in the treatment of diseases is so much that Sheikh Al-Rais.…”
Section: Introductionmentioning
confidence: 99%
“…In Iranian traditional medicine (ITM), prevention of diseases is considered as the priority (1). Based on Avicenna's point of view, it is necessary to consider treatment by three methods: change in the six essentials of life, the employment of medications, and manipulation (2). It is observed that lifestyle modification is a reasonable method in primary healthcare to lessen weight, blood glucose level, belly fat amount, and psychological distress (3).…”
Section: Introductionmentioning
confidence: 99%
“…Although these lifestyle modifications are similar to traditional principles of traditional medicine, ITM provides these strategies with regard to each individual's physical characteristics. One of the basic strategies to improve the quality of life is to educate lifestyle modification based on the ITM that should be considered as the World Health Organization defined health as a state of complete physical, mental, and social well-being and not merely the absence of disease or infirmity (1)(2)(3)(4)(5)(6). Although such approaches are similar both in lifestyles relied on traditional and modern medicines, these approaches in ITM are presented with regard to temporal and personal characteristics of each individual; hence, the ITM has a comprehensive performance.…”
Section: Introductionmentioning
confidence: 99%